Caribbean migration in a global economy - Palmer, Ransford (USIS GeorgetownGY, 1993)
Argues that even if U.S. policy had succeeded in stimulating economic growth and reducing the region's high unemployment rate, it would not have succeeded in reducing the propensity to migrate any significant way because of a combination of factors viz. the historical perception by Caribbean workers of their labour market as global; the monopsonistic structural domestic labour markets; the particular nature of Caribbean migration; and the demand for Caribbean workers in a changing United States economy.